Kinetika Adsorpsi Zat Warna Malachite Green pada Silika Xerogel Hasil Sintesis Abu Terbang - Riska Himaylia Putri; Edi Nasra (Lembaga Yasin AlSys, 2025)
The increasing activity of the textile industry has led to a surge in wastewater containing synthetic dyes such as Malachite Green, which are toxic and resistant to natural degradation. This study aims to investigate the adsorption kinetics of Malachite Green using silica xerogel synthesized from fly ash as an environmentally friendly adsorbent. The synthesis was conducted using the sol-gel method, involving washing with 3 M HCl, extraction with 7 M NaOH, and re-precipitation using HCl until hydrogel formation, followed by drying to produce xerogel. XRF analysis showed an increase in SiO₂ content from 44.06% to 69.09%, indicating successful silica purification. Adsorption tests revealed a maximum capacity of 21.329 mg/g with an optimal contact time of 90 minutes. Kinetic analysis indicated that the adsorption process followed a pseudo-second-order model with an R² value of 0.983, suggesting a chemisorption mechanism involving interactions between silanol groups (-SiOH) on the xerogel surface and dye molecules. These findings demonstrate that fly ash-based silica xerogel has significant potential as an effective, sustainable, and economical adsorbent for dye wastewater treatment in the textile industry.